Zyllt in coronary atherosclerosis patients after coronary artery bypass graft surgery. Preliminary results of an open, randomized, comparative ZEUS Study - Y. I. Grinstein; E. A. Savchenko; I. V. Filonenko; I. Yu. Grinstein1; A. A. Savchenko (Кардиоваскулярная терапия и профилактика)
Aim. To compare clopidogrel and acetylsalicylic acid (ASA) on vasculo-platelet and coagulation hemostasis; to assess the prevalence of laboratory resistance to these agents; and to study 3-month prognosis in coronary heart disease (CHD) patients after coronary artery bypass graft (CABG) surgery.Material and methods. In total, 94 CHD patients, 45-72-year-old males with initially elevated platelet aggregation with ADPH 5mM (PAADPH) and adrenalin 10 mcg/ml (PAAdr), were randomized into two treatment groups, receiving clopidogrel (75 mg/d; n=44) or ASA (75-100 mg/d; n=50). In all participants, parameters of vasculo-platelet and coagulation hemostasis were measured before CABG, 12-14 days and 3 months after CABG. The patients not responding to two-week monotherapy were regarded as resistant. During three-month follow-up period, the incidence of adverse coronary events and pharmacotherapy complications were assessed.Results. Positive dynamics of vasculo-platelet and coagulation hemostasis was observed during clopidogrel or ASA treatment: fibrinogen level was significantly lower in clopidogrel group that in ASA group; 12-14 days and 3 months after CABG, induced PAADPH intensity was significantly reduced in 100% of the patients receiving clopidogrel; no laboratory resistance was observed. No cases of unstable angina, acute myocardial infarction, or death were registered. In those receiving ASA, induced PAADPH was elevated in 24% (n=12) 12-14 days and 3 months after CABG (ASA-resistant subjects), and in 76% (n=38) in reduced by three times (ASA-sensitive subjects). Major or minor hemorrhages, allergic reactions to clopidogrel or ASA were not registered.Conclusion. In patients after CABG, no cases of laboratory resistance to Clopidogrel ("Zyllt", KRKA) were registered; moreover, cardiovascular prognosis was better in clopidogrel group.